Spatially Resolved Characteristic of the Merging Galaxy VV114 as Seen by ALMA - Azeez, Jazeel H. (Iraqi Journal of Science, 2024)
Merging galaxies provide an excellent laboratory for investigating several physical properties related to the merging processes. In this research, high-resolution 12CO (J= 1 – 0) data of the molecular gas was reported in the merging galaxy VV114 from the Atacama Large Millimetre/Sub-millimetre Array (ALMA) to study some of the physical characteristics at the sub-kpc scale. Infrared (IR) data from the Spitzer Space Telescope was used to determine the star formation rate (SFR) and were compared with the properties of the molecular gas. The molecular gas map was divided into 12 regions with a scale of (500 – 600) pc in the CO (1 – 0) integrated intensity and velocity dispersion map. The findings showed a low value for the index of the star formation law for both northeast VV114E and southwest VV114W regions, this may be due to a strong turbulent pressure that could restrict star-formation activity in galaxies at hundreds-parsec scales, causing the Kennicutt-Schmid (KS) law power index to reduce. A significant positive correlation between CO (1 – 0) luminosity surface density and velocity dispersion. The correlation between the SFR surface density and the velocity dispersion was moderate for the VV114E and strong for the VV114W.